Calibration of a hydrological model and sensitivity analysis of its parameters: a case study of Seonath river basin. (6th November 2019) - Verma, Mani Kant; Verma, Mukesh Kumar
The objective of this paper is surface runoff estimation of the Seonath river basin using a semi-distributed hydrological model, i.e., soil and water assessment tool (SWAT). In this paper, the study on calibration and sensitivity is carried out using SWAT-CUP (calibration and uncertainty program) along with sequential uncertainty fitting (SUFI-2) algorithm. The performance of SWAT model is evaluated by various statistical measures; such as Nash-Sutcliffe (NS) coefficient, coefficient of determination (R 2 ), percent bias (Pbias), p factor, r factor and ratio of the root-mean-square error (RMSE) to the standard deviation of the observation (RSR). In the current work, 31 years (1980-2010) of weather data was used. The time slice for model calibration was 15 years, i.e., 1987-2001 with seven years of warming period 1980-1986 and validation period was comprised of nine years (2002-2010). In the study, the calibration of the model was done for the two stations which is a major step for carrying out further study related to climate and land use change impact assessment. The study yielded satisfactory results in terms of model performance.